ANALISIS PERTIMBANGAN KEBIJAKAN LUAR NEGERI RI MELALUI INISIASI ASEAN OUTLOOK ON THE INDO-PACIFIC DI TAHUN 2017-2021: SEBUAH TINJAUAN POLIHEURISTIK - Angga Santa Gideon (2022)
The rise of the Asian Century gave birth to a phenomenon called the Indo-Pacific. The contestation between the United States and China is the only issue on the spectrum of world geopolitical attention. Indonesia and ASEAN as actors in this effort seek to be involved in regional efforts and prevent open conflict between the United States and China. Through the ASEAN Outlook on the Indo-Pacific, Indonesia initiated this policy with efforts to achieve transparency, inclusiveness, positivity, compliance, and compliance with international law based on ASEAN Led-Mechanism in the Indo-Pacific. By using qualitative-descriptive research methods and data sources derived from interviews and library search studies. The theories and concepts used in this study are Foreign Policy and the Concept of Poliheuristic Policy Considerations. The authors' results from this study are that there are two alternative foreign policy alternatives for Indonesia in the Indo-Pacific, Indonesia prefers to rely on ASEAN rather than having to move independently from ASEAN. These policy choices are measured in terms of political, economic, and security dimensions.